Parateoria Kalifornijska Szkoła z Irvine - Bobrowska, Ewa (Nowa Humanistyka, 2013)
Through an intelligent and sharp description of the Irvine School of Critical Theory, Ewa Bobrowska's book significantly expands the knowledge about post-structuralist critical thinking that has dominated the Western humanities in the last quarter of a century. While the achievements of Derrida, Lyotard, Iser, as well as Jameson, Joseph Hillis Miller, Greenblatt, and Dominick LaCapra are well known in Polish critical thought, the interdisciplinary project called the Irvine School has not yet been systematically and competently described. . . . The unusual dispositions of the author, who is an English philologist, philosopher, art historian, and an active artist, allow her to carry out all dimensions of the analysis, including critical discourse, philosophical reasoning, and an intellectual examination of a work of art. Ewa Bobrowska's book can be read in several ways: as a guide to contemporary (mainly American) art that requires participation, and as a guide to contemporary (mainly postmodern) philosophy while visualising some, even very abstract, statements. These two diverse fields of contemporary art discourse and philosophy meet in this work and illuminate each other, giving the reader an extraordinary opportunity to understand the contemporary world of images and ideas. What is particularly worth emphasising is the part of the work that refers to ethical threads: it shows a little-known part of contemporary philosophy and, at the same time, the author's extraordinary sensitivity. (excerpt from a review by Prof. Grażyna Borkowska)